THE ROLE OF TEACHER IN ONLINE LEARNING TO RISE THE STUDENTS INTEREST IN ELEMENTARY SCHOOL OF KEDUNGSARI VILLAGE - Ratna Ro’ifah; Ika Ari Pratiwi; Erik Aditia Ismaya (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research in Kedung Sari Village with 17 research subjects consisting of elementary school students and elementary school teachers in Kedungsari Village. This research was conducted from 5 October – 14 October 2020. The data in this study were obtained orally or in writing. Oral data is obtained based on the results of interviews conducted with sources. The results showed that the roles played by the teachers of Kedungsari Village in increasing student interest in learning were: a) As a teacher, demonstration act as an educator and teacher. b) As a learning manager. The teacher can manage the class well during the online learning process. c) As a mediator and facilitator. During this pandemic, the teacher tries to establish communication with all students and parents. Besides that, the teacher can also become a facilitator for students. d) As an evaluator. The teacher must be a role model for a student to increase student interest in learning and evaluate the learning outcomes achieved.